Validation of a Chinese version of Zohar and Luria’s shortened safety climate measure - Kao, Kuo-Yang; Hsu, Hao-Hsin; Li, Cheng-Hsien; Huang, Yueng-hsiang; Tai, Ning (Current psychology (New Brunswick, N.J.), 2023)
Previous studies have shown that safety climate, as the perceived priority in organizations, is associated with occupational accidents and injuries. Although a few safety climate measures have been developed to meet the needs of different industries in Taiwan, a general safety climate measure in Chinese is still not available. This study aimed to examine the validity and reliability of a Chinese safety climate measure translated from a shorter version of (Zohar and Luria’s Journal of Applied Psychology , 90 (4), 616-628, 2005 ) safety climate measure. After excluding 35 invalid responses, 513 employees working in 61 teams in four companies from the transportation ( N = 108), high-tech ( N = 253), construction ( N = 95), and manufacturing ( N = 57) industries participated in the current study, with a response rate of 92.54% (out of 590 distributed questionnaires). The results showed that a Chinese version of (Zohar and Luria’s Journal of Applied Psychology , 90 (4), 616-628, 2005 ) shortened safety climate measure had high reliability and satisfactory validity with safety motivation, safety-specific transformational leadership, safety behaviors (criterion-related validity), and other safety climate measures (convergent validity) at the individual and team levels. Therefore, this measure can be used as a reliable and effective assessment tool for monitoring occupational safety across industries in Taiwan.